Hedging of Price Risks on Petrochemicals. Case of Retal Industries Ltd. - Potapov, Denis; Taušer, Josef; Čajka, Radek, 1983-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
This thesis presents the hedging theory and its application in order to create an optimal hedging strategy for Retal Industries Ltd. on the PET market. Through this work the hedging theory is tested and assessed basing on its relevance for actual business needs.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses